Modeling of non-linear rheological behavior of hard rock using triaxial rheological experiment - Zhao, Yanlin; Wang, Yixian; Wang, Weijun; Wan, Wen; Tang, Jinzhou (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2017)
This paper presents an extensive laboratory investigation of the non-linear rheological mechanical characteristics of hard rock under cyclic incremental loading and unloading. A data processing algorithm is proposed to analyze the experimental data, determine the instantaneous elastic and plastic strain components, visco-elastic and visco-plastic strain components from the total strain, and separate the visco-elastic and visco-plastic strain curves from the total creep strain curves. The elasto-viscoplastic rheological behavior of iherzolite specimens at various confining pressures is thoroughly studied using the obtained experimental data. Based on the data, a non-linear elasto-viscoplastic rheological model containing various deformation components is proposed, by connecting a Hooke body, a parallel combination of Hooke and plastic slide bodies, a Kelvin body, and a generalized Bingham body. The proportion of instantaneous plastic strain component in the total instantaneous strain has increasing tendency with higher deviatoric stress on a whole. The instantaneous elastic modulus of specimen tends to increase with higher deviatoric stress and confining pressure, the instantaneous plastic modulus of specimen is decreased with higher deviatoric stress at confining pressures of 3 and 6MPa on the whole, however, has no evident relationship with deviatoric stress, when confining pressure is increased to 9 and 16MPa. The proportion of the visco-plastic strain component in the creep strain is increased with higher deviatoric stress. The steady-state creep strain rate versus deviatoric stress relationship can be well described with an exponential expression. The elasto-viscoplastic characteristics of radial creep is similar to that of axial creep, but radial creep strain is only 25–30% of axial creep strain, steady-state creep rate in radial direction is about 35% of that in axial direction. •A data processing algorithm was proposed to analyze the experimental data under cyclic incremental loading and unloading to determine elasto-viscoplastic strain components, and separate the visco-elastic and visco-plastic strain curves from the total creep strain curves.•The proportion of the visco-plastic strain component in the creep strain is increased with higher deviatoric stress. The steady-state creep strain rate versus deviatoric stress relationship can be well described with an exponential expression.•A nonlinear EVPR model containing various deformation components is proposed, which can describe the loading and unloading creep behavior well and give a precise description of the full stages of creep, especially the tertiary creep stage.